The cultivation environment influences the physiological quality of stored Sonchus oleraceus L. seeds (Research, Society and Development, 2022)
Understanding the responses of seeds to the detriment of the interaction of external factors is one of the challenges of research, especially with little explored species such as Sonchus oleraceus L. Thus, the objective was to investigate the effect of the cultivation system, storage time and temperature on the physiological potential of seeds of Sonchus oleraceus L. Seeds were used of two cultivation systems (organic and conventional) in three storage times (0, 90 and 180 days) and submitted at two temperatures (20 and 30 ºC). For the evaluation of germination, the first count, germination percentage and germination speed index were determined, while root length and hypocotyl growth were determined for the evaluation of seedling growth. The first count was statistically higher than 180 days in both crops and temperatures. The seeds of conventional cultivation obtained higher germination percentage and germination speed index at 30 ºC. There was a reduction in root and hypocotyl growth at 180 days, especially at 20 °C. The cultivation environment influences the seed quality of Sonchus oleraceus L. during storage.